Analisis Pengendalian Kualitas Part Cap Front dengan Metode Seven Tools di PT KMIL - Kurniawan, Agung Dwi; Nugraha, Asep Erik (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2025)
PT Kurnia Mustika Indah Lestari (KMIL) is a company engaged in stamping and dies maker that produces several parts for motorbikes and cars. One of the parts produced by the company is the part cap front. Where in the production process, the part cap front often produces defective parts every day. So this study aims to analyze the factors causing defects in the part cap front and to provide suggestions for quality improvements. This study uses the seven tools method used to analyze data. The data used in this study comes from the part cap front production data for the period January 2024. The findings of this study indicate that there are two types of defects in the part cap front, namely oblique welding and scratch. From the results of the pareto diagram, it is known that oblique welding defects are the most dominant defects with 66%. The control chart p used to analyze the control limits produced UCL 0,015 and LCL 0,011. Factors to determine the cause of defects in the fishbone diagram are human factors, machines, methods, materials, and the environment. The proposed improvements in this study are to provide training to operators to improve their skills, routinely carry out machine maintenance schedules, and always pay attention to the SOPs set by the company.